5-Alkylamino-N-phenylpyrazine-2-carboxamides: Design, Preparation, and Antimycobacterial Evaluation - Ambrożkiewicz, Weronika; Kučerová-Chlupáčová, Marta; Janďourek, Ondřej; Konečná, Klára; Paterová, Pavla; Bárta, Pavel; Vinšová, Jarmila; Doležal, Martin; Zitko, Jan (Molecules (Basel, Switzerland), 2020)
According to the World Health Organization, tuberculosis is still in the top ten causes of death from a single infectious agent, killing more than 1.7 million people worldwide each year. The rising resistance developed by Mycobacterium tuberculosis against currently used antituberculars is an imperative to develop new compounds with potential antimycobacterial activity. As a part of our continuous research on structural derivatives of the first-line antitubercular pyrazinamide, we have designed, prepared, and assessed the in vitro whole cell growth inhibition activity of forty-two novel 5-alkylamino-N-phenylpyrazine-2-carboxamides with various length of the alkylamino chain (propylamino to octylamino) and various simple substituents on the benzene ring. Final compounds were tested against Mycobacterium tuberculosis H37Ra and four other mycobacterial strains (M. aurum, M. smegmatis, M. kansasii, M. avium) in a modified Microplate Alamar Blue Assay. We identified several candidate molecules with micromolar MIC against M. tuberculosis H37Ra and low in vitro cytotoxicity in HepG2 cell line, for example, N-(4-hydroxyphenyl)-5-(pentylamino)pyrazine-2-carboxamide (3c, MIC = 3.91 µg/mL or 13.02 µM, SI > 38) and 5-(heptylamino)-N-(p-tolyl)pyrazine-2-carboxamide (4e, MIC = 0.78 µg/mL or 2.39 µM, SI > 20). In a complementary screening, we evaluated the in vitro activity against bacterial and fungal strains of clinical importance. We observed no antibacterial activity and sporadic antifungal activity against the Candida genus.
Keywords: Microbial Sensitivity Tests; Pyrazinamide; Pyrazines; Humans; antituberkulotika; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; antimycobacterial; pyrazinamide; mikrobiální testy citlivosti; lidé; pyrazinamid; vyvíjení léků; Drug Design; Antitubercular Agents; alkylamino derivatives; Mycobacterium tuberculosis; racionální návrh léčiv; antibacterial; pyraziny; cytotoxicity; Drug Development; antifungal